PENDIDIKAN TAREKAT PERSPEKTIF KH. ACHMAD ASRORI AL-ISHAQY DAN RELEVANSINYA TERHADAP TUJUAN PENDIDIKAN NASIONAL - Nashiruddin, Nashiruddin (Mahad Aly Al Fithrah Press, 2018)
Life in modern times is often lulled by a lifestyleglamorous. As a result the heart is easily caught up in the mental illness and increasinglyempty of serenity. Therefore, a doctor is neededexperts in their fields to deal with these problems.Doctors in this case are Sufi scholars who have teacher titlestarekat. KH. Achmad Asrori al-Ishaqi is one of the teacherstarekat whose teachings are currently developing. However, stillthere are some people who think that lifestyleclosely inhibiting one's creativity, because in itteaches to keep away from worldly affairs, which it does notin accordance with the national education goals that sound